Analysis of Elderly Group Community Nursing Practices with Education Innovation Interventions of LSM (Lansia Sehat Merata) among Elderly with Hypertension - Agisti Raudlatul Fitri; Aneng Yuningsih; Reni Hertini (Genius Journal, 2023)
Elderly is a natural process accompanied by a decrease in physical, psychological and social conditions that interact with each other. The attachment of conditions that influence each other causes the elderly to be included in a vulnerable group that needs more monitoring than other age groups. High blood pressure is considered a major risk factor for developing heart disease and various vascular diseases in older people. Through health education efforts, people behave or adopt health behaviors by way of persuasion, appeals, solicitations, and so on. The purpose of this paper is to analyze community nursing care for elderly groups with educational innovation interventions (NGOs) for hypertensive elderly people on the level of knowledge in Sodong Hamlet, Tambaksari Village, Tambaksari Health Center Working Area in 2022. The population used is all hypertensive elderly in Sodong Hamlet, Tambaksari Village, as many as 155 people. The sampling method for nursing care is non-probability sampling. While the technique used is accidental sampling. The results of the nursing analysis found that there was an effect of health education on the level of knowledge in elderly hypertensives after educational interventions were carried out Lansia Sehat Merata.